The Early Childhood Education and International Organizations: When Focus is not Prioritize - Campos, Rosânia (Education Policy Analysis Archives, 2013)
The objective of this paper is analyzing the indications for childhood education in three projects implemented in Latin America: the Ibero-american Agenda for Childhood and Adolescence (Agenda Iberoamericana para a Infância e a Adolescência), the Ibero-american Education Program (Programa Iberoamericano de Educação) and the Regional Education Program for Latin America and Caribbean (Projeto Regional de Educação para América Latina e Caribe), respectively organized by OEI, OEA and UNESCO. Through the political analysis of Roger Dale and the studies of Shiroma, Campos and Garcia in order to analyze the selected documents, this study is based on the relationship among the projects analyzed, the childhood education is an important strategy to “defeat poverty” and one means to promote the equity. The emphasis is placed on compensatory and focal measures designated to children and families in “vulnerable situations” bringing distance and reinforcing the conception of the child education as a public good and as a right for all the children and families.